Teaching and Learning Strategies to Maximize the Operational Curriculum in Learning a Foreign Language: Two Case Studies with Hard-of-Hearing Students - Rojas Pinto, Jennifer Kristine (2023)
This paper gathers the personal and academic experiences of theinclusion of a deaf and a hard-of-hearing students who took the integrated English courses for other majors I and III offered by the Service Courses Area of the School of Literature and Language Sciences (ELCL Spanish acronym) of the Universidad Nacional in Costa Rica. For this purpose, the professors share the practices and transformation processes of teaching and learningexperienced with these students and their interaction with their peers in the classroom as well as the required class management. According to the experiences evidenced, it is concluded that more information is required about the process of learning and teaching English as a foreign language for the deaf and hardof-hearing learners to achieve the transformation and flexibility of the operational and hidden curriculum in a more effective way to maximize an inclusive living, healthy and successful class living.